Fabrication and characterization of alumina/graphenebased ceramics via sol-gel and reactive spark plasma sintering method - Rios Andagoya, Lady Jaqueline (2021)
The fabrication of advanced ceramic matrix composites (CMCs) with low-dimensional carbón allotropes phases is currently an open research topic. One of the modern challenges still remains to overcome common experimental issues, regarding the homogeneity of the nanocarbon dispersion, their location within the ceramic matrix, and the type of bonding between the ﬁller and the matrix. This work introduces the fabrication of fully-dense alumina/graphene ceramic matrix composites by the sol-gel route and reactive spark plasma sintering, as an alternative methodology to improve the dispersion of the graphene ﬂakes within the composite, and to promote the formation of strong bonds between graphene ﬂakes and the ceramic matrix such as Al-O-C oxygen bridges. The micro/nano structures are researched by: nitrogen physisorption, Raman spectroscopy, electron microscopy and X-ray Photoelectron Spectroscopy (XPS). SEM observations revealed the absence of graphene agglomerations suggesting the eﬃcacy of this abrication approach. Raman analyses have conﬁrmed the integrity of the graphene along the abrication process. Mechanical features such as hardness, and indentation fracture toughness ere measured for diﬀerent graphene contents. Our results are compared with those from conventional alumina/graphene CMCs, and suggest that the current approach would oﬀer an appealing route to fabricate reinforced alumina/nanocarbon based ceramics.